Anti-inflammatory effects of nicotinic acid in adipocytes demonstrated by suppression of fractalkine, RANTES, and MCP-1 and upregulation of adiponectin. - Digby, J; McNeill, E; Dyar, O; Lam, V; Greaves, D; Choudhury, R (2010)
OBJECTIVE: A major site of action for the atheroprotective drug nicotinic acid (NA) is adipose tissue, via the G-protein-coupled receptor, GPR109A. Since, adipose tissue is an active secretory organ that contributes both positively and negatively to systemic inflammatory processes associated with cardiovascular disease, we hypothesized that NA would act directly upon adipocytes to alter the expression of pro-inflammatory chemokines, and the anti-inflammatory adipokine adiponectin. METHODS AND RESULTS: TNF-alpha treatment (1.0ng/mL) of 3T3-L1 adipocytes resulted in an increase in gene expression of fractalkine (9+/-3.3-fold, P<0.01); monocyte chemoattractant protein-1 (MCP-1) (24+/-1.2-fold, P<0.001), 'regulated upon activation, normal T cell expressed and secreted' (RANTES) (500+/-55-fold, P<0.001) and inducible nitric oxide synthase (iNOS) (200+/-70-fold, P<0.05). The addition of NA (10(-4)M) to TNF-alpha-treated adipocytes attenuated expression of fractalkine (50+/-12%, P<0.01); MCP-1 (50+/-6%, P<0.01), RANTES (70+/-3%, P<0.01) and iNOS (60+/-16%). This pattern was mirrored in protein released from the adipocytes into the surrounding media. The effect on gene expression was neutralised by pre-treatment with pertussis toxin. NA attenuated macrophage chemotaxis (by 27+/-3.5%, P<0.001) towards adipocyte conditioned media. By contrast, NA, (10(-6)-10(-3)M) increased, in a dose-dependent manner, mRNA of the atheroprotective hormone adiponectin (3-5-fold n=6, P<0.01). CONCLUSIONS: NA suppresses pro-atherogenic chemokines and upregulates the atheroprotective adiponectin through a G-protein-coupled pathway. Since adipose tissue has the potential to contribute to both systemic and local (perivascular) inflammation associated with atherosclerosis our results suggest a new "pleiotropic" role for NA.